ANALISIS PENGARUH KOMUNIKASI ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA PERUM TANI DIVISI REGIONAL JAWA TENGAH) - Aulia, Imam (Laporan Penelitian dan Pengabdian Masyarakat, 2024)
Abstract: This study aims to prove whether there is a direct effect of organizational communication and job satisfaction on performance. Design / methodology / approach: this research is a survey research involving 79 respondents; These respondents represent 380 employees of the Central Java Regional Division of Perum Tani. Research Limitations: This study has limitations using only two independent variables, namely organizational communication and job satisfaction; In addition, employees are also worried about disclosing facts that they experience in the field. Respondents also have limitations related to their many kind education levels. Originality / value: in testing the influence of organizational communication on performance, the value of the standard beta coefficient is 0.923 (positive) so it can be concluded that the organizational communication variable has a significant effect on the performance variable. In testing the effect of job satisfaction on performance, the standard beta coefficient value obtained is 0.938 (positive) so it can be concluded that job satisfaction has an influence on performance. Keywords: organizational communication, job satisfaction, performance